1995
DOI: 10.1073/pnas.92.26.12441
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine activates ATP-sensitive potassium channels in arterial myocytes via A2 receptors and cAMP-dependent protein kinase.

Abstract: The mechanism by which the endogenous vasodilator adenosine causes ATP-sensitive potassium (KATp) channels in arterial smooth muscle to open was investigated by the whole-cell patch-clamp technique. Adenosine induced voltage-independent, potassium-selective currents, which were inhibited by glibenclamide, a blocker of KATP currents. Glibenclamide-sensitive currents were also activated by the selective adenosine A2-receptor agonist 2-p-(2-carboxethyl)-phenethylamino-5'-N-ethylcarboxamidoadenosine hydrochloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
151
4
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(171 citation statements)
references
References 41 publications
(43 reference statements)
13
151
4
1
Order By: Relevance
“…Treatment of islets with antisense ODNs reduced both GLP-1-and GIPpotentiated insulin secretion, clearly indicating that the effects of the incretins are mediated in part by cAMP-GEFII. Ten M of H-89, a widely used specific inhibitor of PKA phosphorylation in intact cells (24,28,41,50), was then used to block the phosphorylation of GLUT2, a substrate of PKA in pancreatic ␤-cells (28), to evaluate incretin-potentiated insulin secretion. Interestingly, although treatment of pancreatic islets with H-89 reduced (about 50%) both GLP-1-and GIP-potentiated insulin secretions, treatment of the islets with H-89 plus antisense ODNs further reduced the insulin secretions (80 -90%), suggesting strongly that the potentiation of insulin secretion by both GLP-1 and GIP is mediated by PKA-independent as well as PKA-dependent mechanisms and that cAMP-GEFII is involved in the PKA-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of islets with antisense ODNs reduced both GLP-1-and GIPpotentiated insulin secretion, clearly indicating that the effects of the incretins are mediated in part by cAMP-GEFII. Ten M of H-89, a widely used specific inhibitor of PKA phosphorylation in intact cells (24,28,41,50), was then used to block the phosphorylation of GLUT2, a substrate of PKA in pancreatic ␤-cells (28), to evaluate incretin-potentiated insulin secretion. Interestingly, although treatment of pancreatic islets with H-89 reduced (about 50%) both GLP-1-and GIP-potentiated insulin secretions, treatment of the islets with H-89 plus antisense ODNs further reduced the insulin secretions (80 -90%), suggesting strongly that the potentiation of insulin secretion by both GLP-1 and GIP is mediated by PKA-independent as well as PKA-dependent mechanisms and that cAMP-GEFII is involved in the PKA-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The role of voltage-dependent K ϩ (K V ) channels in adenosine-mediated relaxation has not been reported previously; however, findings of Aiello et al (1,2) provide evidence that both protein kinase A (PKA) and isoproterenol stimulate K V channels in isolated vascular smooth muscle cells. Although controversial, adenosine has been reported to act via cAMP and PKA in vascular smooth muscle (16), providing a putative mechanism for K V -channel activation by adenosine.…”
mentioning
confidence: 99%
“…Indeed, it was previously observed that these A 2 receptor subtypes are expressed in the mesenteric vascular bed, although A 2B receptors are weakly expressed in comparison to A 2A receptors [71]. A 2A receptor-mediated vasodilatory effects have been observed in the rat and rabbit mesenteric artery [31,64,79,133]. These effects appear to involve the opening of potassium channels subsequent to A 2A receptor activation.…”
Section: Adenosine Receptors In the Splanchnic Circulationmentioning
confidence: 99%
“…As previously referred, A 2 receptors are coupled to G s proteins, which activate adenylyl cyclase leading to an increase in intracellular cAMP. The elevation of cAMP further activates protein kinase A, which opens potassium channels probably through a phosphorylation step [79].…”
Section: Adenosine Receptors In the Splanchnic Circulationmentioning
confidence: 99%